Synthesis of γ-cyclodextrin substituted bis(acyl)phosphane oxide derivative (BAPO-γ-CyD) serving as multiple photoinitiator and crosslinking agent. Issue 35 (1st April 2020) - Cosola, Andrea; Conti, Riccardo; Rana, Vijay Kumar; Sangermano, Marco; Chiappone, Annalisa; Levalois-Grützmacher, Joëlle; Grützmacher, Hansjörg
Abstract : Cyclodextrin with up to 10 bis(acyl)phosphanoxide functions serves as an initiator for highly cross-linked swellable hydrogels from mono-acrylates. Abstract : A new multi-photoactive γ-cyclodextrin substituted bis(acyl)phosphane oxide derivative (BAPO-γ-CyD) was successfully prepared via a convergent synthesis using a phospha-Michael-addition, as confirmed by 1 H-, 13 C-, 31 P-NMR and IR spectroscopy and mass spectrometry. Kinetic studies carried out by photo-DSC and photo-rheology demonstrated its outstanding efficiency as a photoinitiator for free-radical polymerization. Remarkably, it is found that BAPO-γ-CyD also acts as a crosslinking agent to convert monofunctional methacrylate monomers into self-standing thermosetting networks with extensive swelling capability in water.